Towards high spatial resolution tissue‐equivalent dosimetry for microbeam radiation therapy using organic semiconductors. (8th July 2021) - Posar, Jessie A.; Large, Matthew; Alnaghy, Saree; Paino, Jason R.; Butler, Duncan J.; Griffith, Matthew J.; Hood, Sean; Lerch, Michael L. F.; Rosenfeld, Anatoly; Sellin, Paul J.; Guatelli, Susanna; Petasecca, Marco
Abstract : This work presents the first characterization of a thin organic semiconductor photodiode for dosimetry in microbeam radiation therapy carried out on the Australian Synchrotron Imaging and Medical Beamline. Abstract : Spatially fractionated ultra‐high‐dose‐rate beams used during microbeam radiation therapy (MRT) have been shown to increase the differential response between normal and tumour tissue. Quality assurance of MRT requires a dosimeter that possesses tissue equivalence, high radiation tolerance and spatial resolution. This is currently an unsolved challenge. This work explored the use of a 500 nm thick organic semiconductor for MRT dosimetry on the Imaging and Medical Beamline at the Australian Synchrotron. Three beam filters were used to irradiate the device with peak energies of 48, 76 and 88 keV with respective dose rates of 3668, 500 and 209 Gy s −1 . The response of the device stabilized to 30% efficiency after an irradiation dose of 30 kGy, with a 0.5% variation at doses of 35 kGy and higher. The calibration factor after pre‐irradiation was determined to be 1.02 ± 0.005 µGy per count across all three X‐ray energy spectra, demonstrating the unique advantage of using tissue‐equivalent materials for dosimetry. The percentage depth dose curve was within ±5% of the PTW microDiamond detector. The broad beam was fractionated into 50 microbeams (50 µm FHWM and 400 µm centre‐to‐centre distance). For each beam filter, the FWHMs of all 50 microbeams were measured to be 51 ± 1.4, 53 ± 1.4 and 69 ± 1.9 µm, for the highest to lowest dose rate, respectively. The variation in response suggested the photodetector possessed dose‐rate dependence. However, its ability to reconstruct the microbeam profile was affected by the presence of additional dose peaks adjacent to the one generated by the X‐ray microbeam. Geant4 simulations proved that the additional peaks were due to optical photons generated in the barrier film coupled to the sensitive volume. The simulations also confirmed that the amplitude of the additional peak in comparison with the microbeam decreased for spectra with lower peak energies, as observed in the experimental data. The material packaging can be optimized during fabrication by solution processing onto a flexible substrate with a non‐fluorescent barrier film. With these improvements, organic photodetectors show promising prospects as a cost‐effective high spatial resolution tissue‐equivalent flexible dosimeter for synchrotron radiation fields.